PENGGUNAAN PASIR ALAM KALIMANTAN TENGAH UNTUK CAMPURAN BETON ASPAL LAPIS PERMUKAAN - Nono Nono (Jurnal Jalan-Jembatan, 2009)
From years to years the use of aggregate for maintenance and new pavement construction increases, while the resources of crushed stone decrease. Every year the need of aggregate to use for pavement construction in Central Kalimantan is increased. This research is based on the use of natural sand from Central Kalimantan for asphalt concrete wearing course (ACWC). To evaluate the performance of asphalt mixture in the laboratory, the test conducted in this research was Marshall Test. The result shown that the use of the natural sand up to 37% from the total weight of asphalt mixture, was still conform to the specification. Key words :natural sand, Central Kalimantan, asphalt concrete wearing course